CHARACTERISTICS OF NECROTIZING ENTEROCOLITIS IN NEONATES TREATED AT SANGLAH HOSPITAL - Hartini, Kadek; Artana, Dharma; Putra, Junara (Medicina; Vol 44 No 1 (2013): Januari 2013)
Necrotizing enterocolitis (NEC) is a very serious and severe neonatal gastrointestinal tract disease. Treatment are complex and the course of the disease is hardly predictable. N ecrotizing enterocolitis is one of the main causes of morbidity and mortality in neonates. The objective of this study was t o know the prevalence and characteristics of neonates with NEC . This was a retrospective descriptive study utilizing medical records of neonates who were admitted in perinatology care unit at Sanglah Hospital, Denpasar during the period of July 2011 to June 2012.There were 55 (5%) neonates with NEC out of 972 neonates admitted to the neo natology care unit at Sanglah Hospital, Denpasar. Mean gestational age was 33.9 weeks. Mean birth weight was 2.096 kg,and the mean time of nutrition initiation was 3.1 days. Stage II was found as the most prevalent stage of NEC (49%). Necrotizing enterocolitis patients were generally associated with clinical manifestations such as sepsis 96%, respiratory distress 87% , prematurity 63%, low birth weight 65%, and asphyxia 61%. There was 36 subjects dead. This outcome tended to increase in premature babies, babies with low birth weight, asphyxia , and sepsis. Death still occurred in all management of NEC. Neonates receiving breast milk as the initial nutrition constituted the highest proportion of recovered patients compared to the fasting, formula milk, and mixed milk (breast milk combined with formula milk) groups. We concluded, the prevalence of NEC was 5%. Death more common than recoveries. Recovery rate more common in breast-fed babies than other nutrients Normal 0 false false false IN X-NONE X-NONE /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-qformat:yes; mso-style-parent:""; mso-padding-alt:0cm 5.4pt 0cm 5.4pt; mso-para-margin:0cm; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:"Times New Roman"; mso-fareast-theme-font:minor-fareast; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; mso-bidi-font-family:"Times New Roman"; mso-bidi-theme-font:minor-bidi;} Normal 0 false false false IN X-NONE X-NONE /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-qformat:yes; mso-style-parent:""; mso-padding-alt:0cm 5.4pt 0cm 5.4pt; mso-para-margin:0cm; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:"Times New Roman"; mso-fareast-theme-font:minor-fareast; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; mso-bidi-font-family:"Times New Roman"; mso-bidi-theme-font:minor-bidi;}
Keywords: necrotizing enterocolitis, neonates